Implications of Multiple Disequilibrium Textures in Quartz-Hosted Embayments - Ruefer, Anna C.; Befus, Kenneth S.; Thompson, James O.; Andrews, Benjamin J. (Frontiers in Earth Science, 2021)
The faces of volcanic phenocrysts may be marked by imperfections occurring as holes that penetrate the crystal interior. When filled with glass these features, called embayments or reentrants, have been used to petrologically constrain magmatic ascent rate. Embayment ascent speedometry relies on the record of disequilibrium preserved as diffusion-limited volatile concentration gradients in the embayment glass. Clear, glassy embayments are carefully selected for speedometry studies. The use and subsequent descriptions of pristine embayments overrepresent their actual abundance. Here, we provide a textural analysis of the number, morphology, and filling characteristics of quartz-hosted embayments. We target a collection of large (i.e., >20 km3 erupted volume) silicic eruptions, including the Bishop Tuff, Tuff of Bluff Point, Bandelier Tuff, Mesa Falls Tuff, and Huckleberry Ridge Tuff in the United States, Oruanui Tuff in New Zealand, Younger Toba Tuff in Indonesia, the Kos Plateau Tuff in Greece, and the Giant Pumice from La Primavera caldera in Mexico. For each unit, hundreds of quartz crystals were picked and the total number of embayment-hosting crystals were counted and categorized into classifications based on the vesicularity and morphology. We observed significant variability in embayment abundance, form, and vesicularity across different eruptions. Simple, cylindrical forms are the most common, as are dense glassy embayments. Increasingly complex shapes and a range of bubble textures are also common. Embayments may crosscut or deflect prominent internal cathodoluminescence banding in the host quartz, indicating that embayments form by both dissolution and growth. We propose potential additional timescales recorded by embayment disequilibrium textures, namely, faceting, bubbles, and the lack thereof. Embayment formation likely occurs tens to hundreds of years before eruption because embayment surfaces are rounded instead of faceted. Bubble textures in embayments are far from those predicted by equilibrium solubility. Homogenous nucleation conditions likely allow preservation of pressures much greater than magmastatic inside embayments. Our textural observations lend insight into embayment occurrence and formation and guide further embayment studies.